The Influence of Students’ Perceptions of Learning Models and Self-Efficacy on Critical Thinking Skills in Science - Pujiastuti, Dwi; Suendarti, Mamik; Hasbullah (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Twenty-first-century educational demands emphasize the importance of critical thinking skills. Deficiencies in students' scientific critical thinking, often stemming from traditional teaching methods and poor self-belief, demand the adoption of progressive educational frameworks like Problem-Based Learning. This research was designed to investigate three key relationships among public middle school students in South Tangerang City: (1) the combined influence of model perception and self-efficacy on science based critical thinking, (2) the individual impact of model perception, and (3) the individual impact of self-efficacy. Using a survey design, the study sampled a population of 874 students across Public Junior High School 11 and Public Junior High School 7. The finding indicated that: (1) the combined effect of both variables was statistically significant (Sig. = 0.000 < 0.05; F = 32.686), accounting 42.9% of the variability in critical thinking scores, with other variables explaining the remaining 57.1%; (2) a significant effect on science critical thinking capacities was exerted by perceptions of learning models (Sig. = 0.000 < 0.05; t = 5.843); and (3) self-efficacy also had a significant effect on science critical thinking skills (Sig. = 0.000 < 0.05; t = 5.783). Therefore, perceptions of learning models and self-efficacy are important factors in improving students’ science critical thinking skills.